Kerusuhan Rutan Mako Brimob Kelapa Dua menjadi Katalisator Disahkannya Undang-Undang Nomor 5 Tahun 2018 (Neolectura, 2023)
The ratification of Law Number 5 of 2018 to amend Law Number 15 of 2003 to establish government regulations in lieu of Law Number 1 of 2002 to abolish criminal acts of terrorism would result in the laws being enacted. This demonstrates how committed the government is to eliminating terrorism in order to protect the integrity of the country and state. The purpose of this study is to determine how the disturbance at the Mako Brimob Kelapa Dua Detention Center led to the enactment of Law Number 5 of 2018, what measures were made to avert it, and how successful it was in outlawing terrorist offenses. This study employs normative legal research methodology and descriptive qualitative research techniques. The findings demonstrated that the disturbance at the Mobile Brigade Headquarters Kelapa Dua served as the impetus for the enactment of Law Number 5 of 2018. After a number of terror incidents following the riots, the government urged the DPR to quickly pass Law Number 5 2018, a revision of Law Number 15 of 2003, because of several flaws in the previous Terrorism Law that hindered law enforcement officials' ability to eradicate terrorist crimes in Indonesia.